Numerical analysis of doubler-plate reinforced tubular T-joints under tension and in-plane bending subjected to fire condition - Zhu, Kankang (2014)
To study structural behaviour of doubler plate reinforced tubular T-joints in fire condition; finite element analysis is introduced to perform numerical analysis. A numerical model was constructed with ABAQUS. Modelling strategies of the doubler plate reinforced tubular T-joint were also reported. The joint model was validated by comparing the numerical and experimental load-deformation curves. The validated model was then subjected to total 10 numerical analysis including tension and in-plane moment analysis respectively at 20 °C, 300 °C, 500 °C, 600 °C and 700 °C to determine the load-deformation curves. The ultimate bearing capacities of the joint at the five temperatures were calculated and analysed at Yura’s deformation limit. The failure modes of the T-joint were also discussed. The behavioural study of the tubular joint indicates the relationship between joint performance and temperature.